2018
DOI: 10.1007/s11524-018-0306-y
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Association between Firearm Laws and Homicide in Urban Counties

Abstract: The authors would like to publish this erratum to correct estimates generated from regression analyses due to errors discovered in the coding of some state laws. The following corrections to the laws in Table 1 are warranted: 1) Michigan no longer requires a permit-to-purchase for handgun sales by licensed dealers effective December 18, 2012 (permits are still necessary for private transfers); 2) Connecticut enacted a law prohibiting firearm purchases for violent misdemeanants effective October 1, 1994; and 3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…[48][49][50] Peer (nonpartner) violence is an important contributor to firearm-related morbidity and mortality; indeed, it is the leading cause of death among non-Hispanic, Black American males aged 15 to 34 years. 51,52 Our advisory group prioritized understanding the epidemiology of these injuries 53 ; the role of the social determinants of health 54 ; and evidence-based policies, [55][56][57] programs, 58 and strategies 59 that can reduce peer violence. Our advisory group had consensus that medical professionals should be trained in best practices for screening and counseling victims of peer violence 60 and understand the role and effectiveness of hospital-and community-based violence prevention programs.…”
Section: Discussionmentioning
confidence: 99%
“…[48][49][50] Peer (nonpartner) violence is an important contributor to firearm-related morbidity and mortality; indeed, it is the leading cause of death among non-Hispanic, Black American males aged 15 to 34 years. 51,52 Our advisory group prioritized understanding the epidemiology of these injuries 53 ; the role of the social determinants of health 54 ; and evidence-based policies, [55][56][57] programs, 58 and strategies 59 that can reduce peer violence. Our advisory group had consensus that medical professionals should be trained in best practices for screening and counseling victims of peer violence 60 and understand the role and effectiveness of hospital-and community-based violence prevention programs.…”
Section: Discussionmentioning
confidence: 99%
“…One policy that acts as an implementation mechanism for firearm restrictions is the handgun purchaser licensing law, which generally requires that prospective gun purchasers obtain a background check (regardless of whether they purchase through a private party or a licensed firearms dealer) that often is conducted at a local governmental agency, such as a police department, and can include fingerprinting and other additional safety-focused steps. These laws have been associated with lowered incidence of multiple categories of gun violence (Crifasi et al, 2018; Webster et al, 2020). With research suggesting that nearly half of mass shooters may have gun purchase prohibitions (Zeoli & Paruk, 2020), and evidence that handgun purchaser licensing laws were associated with a significant reduction in gun homicide in large, urban counties (Crifasi et al, 2018), this policy may help reduce both mass shootings and community gun homicides by preventing some would-be shooters from acquiring guns.…”
Section: Interventions To Reduce Gun Homicidementioning
confidence: 99%
“…These laws have been associated with lowered incidence of multiple categories of gun violence (Crifasi et al, 2018; Webster et al, 2020). With research suggesting that nearly half of mass shooters may have gun purchase prohibitions (Zeoli & Paruk, 2020), and evidence that handgun purchaser licensing laws were associated with a significant reduction in gun homicide in large, urban counties (Crifasi et al, 2018), this policy may help reduce both mass shootings and community gun homicides by preventing some would-be shooters from acquiring guns.…”
Section: Interventions To Reduce Gun Homicidementioning
confidence: 99%
See 1 more Smart Citation
“…In studies of permit-topurchase licensing policies, researchers found they were associated with reductions in firearm suicides and homicides [24][25][26][27] but not intimate partner homicide. 28 Conversely, in studies of point-of-sale background checks for private sales, researchers have generally not identified decreases in firearm mortality, [28][29][30][31] although background checks for private sales have been associated with reductions in firearm diversion. 32,33 Finally, given that states may differentially implement policies, analyzing state-level implementation methods is an important consideration for future studies.…”
mentioning
confidence: 99%